Comparison of perioperative outcomes of open (CUSA) versus laparoscopic (LOTUS) major hepatectomy – revisited. First evaluation of efficacy and safety of AEON™ stapler - Iqbal, Affan; Baltatzis, Minas; Stathakis, Panagiotis; Barrie, Jenifer; Siriwardena, Ajith Kumar; Jamdar, Saurabh; Sheen, Aali Jan (Frontiers in Oncology, 2025)
IntroductionIn 2019, preliminary data matching 20 laparoscopic (using LOTUS) with 20 open (using CUSA) cases demonstrated the feasibility and improved outcomes of laparoscopic major liver resections using the LOTUS™ liver blade. This updated study presents a larger comparison between open and laparoscopic major hepatectomies and, for the first time, evaluates the safety of the endovascular stapler AEON™ (Lexington Medical, Massachusetts, USA).MethodsAll consecutive patients who underwent liver resections, both open and laparoscopic, from January 2020 to June 2023 were identified from a prospectively maintained database. Propensity score matching was performed to identify matched open and laparoscopic cases, which were compared for intra- and post-operative short-term outcomes. The LOTUS™ ultrasonic energy device was used for transection in laparoscopic cases, whereas CUSA was used in open procedures. AEON was introduced in 2021 and compared with the previously used stapler.ResultsThe initial sample of 116 patients was narrowed to 86 after applying 1:1 matching. The median age was 63 years (range 27–83). Laparoscopic cases showed reduced hospital stay (mean 7.8 vs. 14.7 days; p = 0.025), increased Pringle time (48.5 vs. 33 minutes; p = 0.010), and reduced transfusion requirements (0 vs. 4 units; p = 0.035). Comparing AEON™ with Endo-GIA showed no statistical differences, though AEON™ showed a possible trend toward reduced transection time overall (56 vs. 69 minutes; p = 0.300) and in laparoscopic cases (56 vs. 71 minutes; p = 0.295).ConclusionThe LOTUS™ liver blade continues to demonstrate safety and efficacy in laparoscopic liver resections. Transection time has improved compared to the earlier study, likely reflecting increased experience. AEON™ is shown to be non-inferior for vessel ligation, with a potential trend toward reduced transection time in both open and laparoscopic cases.